Effect Of Foundation Geometry On Short Abutment Scour - Ghalati, Reza Mohammadpour (2012)
Accurate prediction of the local scour at abutments is an important criterion to design a safe depth for the bridge foundation. An experimental study for predicting local scour around the complex and uniform abutment under clear water conditions is presented. In this research, a short complex abutment included a rectangular abutment and situated on a larger rectangular foundation. The results are presented according to three scour cases. In Case I, the foundation level was located below the scour hole. In Case II, scour depth reaches the top of the foundation, and in Case III, the top of the foundation was located within the scour hole. The results reveal that the scour depth at a complex abutment is dependent on foundation level (Z), length of abutment (L) and the dimensions of the foundation (Lf) in addition to the factors that influence local scour depth at a uniform cross section abutment. Several equations have been developed based on two methods, Multiple Linear Regression (MLR) and effective length, to predict scour depth around a complex abutment. The trend of scour depth development over time around a complex abutment was also investigated. For uniform abutments, the dimension and variation of local scour with time were investigated. The MLR, genetic programming (GP) and artificial neural networks (ANNs), feed forward back propagation (FFBP) and radial basis function (RBF) were used to predict the time variation of scour depth at uniform abutment.